On the Class of (q, α, β)-Metrics. (10th March 2014) - Alimohammadi, Ahmad
Abstract : We study a class of Finsler metrics in the form F = α + β q / α q - 1, where α is a Riemannian metric, β is a 1 -form, and 1 < q < 2 .   F is called ( q, α, β ) -metrics. We find the necessary and sufficient conditions under which the class of ( q, α, β ) -metrics is locally projectively flat and Douglas metrics, respectively.